Development of Service-Oriented Architecture-Based Microservices Management as a Data Integration Service (Case Study: Udayana University) - Jayarana, I Gede Nyoman Agung; Aryanto, Kadek Yota Ernanda; Sunarya, I Made Gede (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 11 No 1 (2023): Vol. 11, No. 1, April 2023, 2023)
Udayana University has developed numerous information systems to accommodate all types of academic and non-academic activities. Because the process of retrieving data from other systems still employs the traditional method with a joint scheme between databases, the resulting data quality becomes increasingly inaccurate over time. Some systems have also established simple web services that do not adhere to the Restful API authoring rules. Based on these issues, modifications were made to the data integration process using Microservices Management, Service Oriented Architecture, and OAuth 2.0 as the security protocol. The results indicate that the microservices management system is highly effective and efficient for improving process performance, has a low risk level, a good control test validation of 93,33 %, and a usability grade of B, indicating that the system is deemed good and usable.